Teacher’s Reinforcements Affecting Students’ Willingness to Communicate (WTC): A Photovoice in EFL Classroom - Bimo Teguh Prasetyanto; Diyah Ayu Wibawani; Erika Novia Wardani; Nur Arifah Drajati (Indonesian Journal of EFL and Linguistics, 2019)
In teaching English, a teacher should stimulate students’ activeness to engage in a class. One way to do it is by giving reinforcement. A good reinforcement has a significant role in the students’ speaking activeness. It can be a source of students’ motivation to learn and in this case, their activeness to speak in class. This research aims to discover what reinforcement that triggers students’ willingness to communicate. The result is intended to discover the effects of teacher’s reinforcement towards students’ willingness to communicate. The data for this research is collected by the photovoice method in which more practical is needed by collaborating with SHOWeD in analyzing the data. The participants of this research are 28 college students, consisting 7 male students and 21 female students ranging from 19 to 21 years old in English Education Department who are currently attending college. Based on the data analysis, the finding of the research is teacher reinforcement in EFL classroom affect students’ willingness to communicate, particularly self-confidence, interpersonal motivation, and intergroup motivation. The research implied to help teachers to understand more about the way teacher’s reinforcement affect the students’ speaking activeness seen from the students’ perspective.